Promotion, recruitment and retention of members in nonprofit organizations - Calderón-Valencia, Cecilia Isabel; Cavazos-Arroyo, Judith; López Lira-Arjona, Alfonso (Emerald Publishing Limited, 2021)
Although research on the value of membership of Nonprofit Organizations (NPOs) is increasing, there remain few theoretical and empirical advances in this area. Addressing this gap, this book offers a fresh perspective, exploring how NPOs' survival is linked to the promotion, recruitment and retention of members. Highlighting the critical role of NPO members in creating value in the pursuit of its missions, this book demonstrates how NPOs must promote active participation and empowerment of its members to facilitate fund raising, financial administration, and the pursuit of alliances. Providing a road map for improvement in recruiting and retention processes, the authors also showcase the development of strategies to motivate potential members and donors, and the part played by the commitment of the board in the achievement of the NPO's social mission. In today's global world, this book is insightful reading for those interested in using coordinated action to navigate adverse scenarios. Written primarily for NPO managers who aim to proactively engage their members in the creation of social value, it is also a valuable resource for researchers interested in the underlying foundations of NPO membership.